A facies- and sequence stratigraphy-based reservoir model for a carbonate reef complex: South Swan Hills oil pool, Alberta. (June 2023) - Noyahr, Christopher V.; Weissenberger, John A.W.; Harris, Nicholas B.; Banks, Jonathan
Abstract: We present a reservoir model for the South Swan Hills oilfield, Alberta, Canada, developed in a Devonian atoll reef, based on facies analysis and sequence stratigraphy. The analysis illustrates the complex reservoir geometries in such a reef, caused by facies variation from reef margin to reef interior and fluctuations in relative sea level. The latter resulted in cyclic deposition of facies and formation of field-scale sequence boundaries. The model is built on lithofacies analysis from high-resolution core descriptions that recorded lithologies, bioclast type and characteristics, and sedimentary structures. Core descriptions were correlated to well logs, enabling lithofacies to be mapped across the field. Lithofacies distributions permit definition of three distinct reef environments: a reef interior, a reef margin and a terminal shoal. Vertical variability is characterized using sequence stratigraphic interpretations. Two 3rd order and four 4th order sequence boundaries were identified and correlated across the reef. The analysis illustrates the complex reef geometries linked to facies variation from reef margin to reef interior and fluctuations in relative sea level. The latter resulted in cyclic deposition of facies and formation of field-scale unconformities. These and the intervening deposits represent the response to fluctuating sea level. The geological analysis was transformed into a 3-D geocellular model using a sequential indicator simulator. The simulator models lithofacies and, in turn, porosity and permeability distributions based on strong relationships between lithofacies and petrophysical properties for the three representative regions; the interior, margin and terminal shoal. The interior deposits formed forms the bulk of non-reservoir material in the centre of the reef build-up. The margin surrounded surrounds the interior and formed forms a continuous 1–2 km band of reservoir around it. Reservoir thickness is 20–30 m and primarily composed of reef flat deposits. The terminal shoal forms a reservoir body that caps the reef complex, but is disconnected from the bulk of the underlying reef by a thick layer of impermeable clay associated with a sequence boundary. The high-resolution realization displays the geometry and continuity of the reservoir and exposes demonstrates the compartmentalized and variable producibility of the atoll. Highlights: Large core and petrophysical dataset transformed into a high-resolution 3-D geomodel of a rim-bounded atoll reef. 3rd, 4th and 5th order sequences predict the accumulation of porous facies. The stochastically realized grid delineates and visualizes complex geometry and continuity of the reservoir geobodies Typified atoll architecture where reservoirs develop at the margin and the terminal shoal.